How Teachers Encourage Students’ Mathematical Reasoning during the Covid-19 Pandemic? - Rohati; Kusumah, Yaya S.; Kusnandi; Marlina (Jurnal Pendidikan Indonesia, 2022)
Students' mathematical reasoning abilities can develop depending on the teacher's involvement in the classroom. The problem that often occurs in the class is that the teacher's actions have not been neatly arranged to encourage students' mathematical reasoning in learning mathematics. This article aims to observe the actions taken by a group of mathematics teachers in encouraging students' mathematical reasoning abilities. This type of research is qualitative research with data collected from learning recordings in the classroom. The research subjects were three junior high school, mathematics teachers. The teacher observed how students reasoned during 12 sessions as they studied and completed homework. The results of observing students' mathematical reasoning activities, such as building reasonable arguments and drawing correct conclusions, were concluded to enable teachers to test their students' mathematical reasoning. The findings of this study indicate that teachers can foster students' mathematical reasoning by applying the following strategies: (a) providing appropriate learning interventions; (b) assigning open tasks without solution methods, and (c) fostering a learning community that values ​​reasoning and the construction of shared ideas.